2017
DOI: 10.5039/agraria.v12i4a5470
|View full text |Cite
|
Sign up to set email alerts
|

Deriva do herbicida 2,4-d aplicado com pontas hidráulicas de jato plano tipo leque

Abstract: RESUMOA deriva é um dos maiores problemas na aplicação de agrotóxicos, responsável, muitas vezes, pela baixa eficiência dos controles. Objetivou-se analisar a deriva do herbicida 2,4-D aplicado com pontas hidráulicas de jato plano tipo leque. Foram avaliadas duas soluções: água e água + 2,4-D e quatro pontas: leque simples (JS), leque simples com pré-orifício (JSPO), leque simples com indução (JSIA) e leque duplo com indução (JDIA). O diâmetro da mediana volumétrica (DMV), a amplitude relativa (SPAN), e a perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Due to the mode of action of these herbicides, it is Rebesquini et al (2024) Physiological and growth responses of... reported that drift situations have shown a high potential for damaging sensitive species, even in small quantities (Godinho Júnior et al, 2017). The matter about potential damage generated by the 2,4-D drift has been growing since the release of genotypes tolerant to this herbicide in some agricultural crops, such as soybeans and cotton, which increased its utilization (Mortensen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the mode of action of these herbicides, it is Rebesquini et al (2024) Physiological and growth responses of... reported that drift situations have shown a high potential for damaging sensitive species, even in small quantities (Godinho Júnior et al, 2017). The matter about potential damage generated by the 2,4-D drift has been growing since the release of genotypes tolerant to this herbicide in some agricultural crops, such as soybeans and cotton, which increased its utilization (Mortensen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide drift is characterized by the displacement of the sprayed product to nearby crops and occurs mainly due to the used drop size (generally less than 100 μm) (Godinho Júnior;Caixeta;Ruas;Faria;Carvalho Filho, 2017), the action of the wind, temperature and relative humidity at the time of spray. The main reason for the drift of these compounds is an incorrect spraying method due to the use of an inappropriate spray tip, inappropriate height of the bar or inadequate application speed (Carlsen;Spliid;Syensmarck, 2006).…”
Section: Introductionmentioning
confidence: 99%